Kinetics Study on Lithium Leaching of Spent Lithium Iron Phosphate Batteries in Low Concentration of Sulfuric Acid - Zaizamshimi Nurul Farah Dyana; Indra Perdana; Agus Prasetya (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2020)
Recovery of valuable metals from spent lithium iron phosphate (LiFePO4) batteries are quite challenging because it needs a lot of process. The recycling of these spent batteries can avoid environment contamination from the waste, meanwhile the valuable metallic components in the batteries including lithium can be treated as a resource for potential recovery of lithium. Low concentration of sulfuric acid (H2SO4) as a leachant and hydrogen peroxide (H2O2) as an oxidant, was used to leach elements from cathode materials of spent LiFePO4 batteries that mainly contained Li, Fe and P. Li could be selectively leached into the solution and while Fe and P was assumed to remain in the residue. The significant effects of acid concentration, solid-liquid ratio, reaction temperature and reaction time on the leaching rate are determined. Under the optimum conditions of 0.1 M H2SO4, 2 vol% H2O2, S/L ratio of 75g/L, 60 °C and 60 min, the leaching efficiency determined were 74.74% for Li and 0.99% for Fe. A leaching mechanism of shrinking-core model with diffusion through product layer control was proposed. It was found that the apparent activation energy was 12.69 kJ mol-1 as calculated by the Arrhenius equation together with an enthalpy (∆H) of 10 kJ mol-1 and an entropy (∆S) of -264.54 Jmol-1K-1.